MANAJEMEN PENINGKATAN KINERJA PEGAWAI BERBASIS E-KINERJA DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN TAKALAR - Sumarlin Mus; Dinar Afriani; Ansar (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study examines how Employe Performance Improvement Management Based on E-Performance at the Education and Culture Office of Takalar Regency. The main focus is on the Management of Employe Performance Improvement and the identification of supporting and hindering factors that emerge. Using a descriptive qualitative method, data was collected thru interviews, observations, and documentation from the head of the department and employes. The validity of the data was examined using triangulation techniques. The research results show that: 1) The planning process, the preparation of SKP, and the action plan are carried out based on the supervisor's instructions. Thus, it is capable of improving employe performance, particularly in terms of discipline and clarity of work. 2) The actuating process shows a structured process, therefore, the E-Kinerja system significantly impacts the improvement of employe performance, especially in aspects of responsibility and task execution quality. 3) The controlling process indicates that structured assessment, feedback provision, and follow-up support employe performance improvement. However, there are technical obstacles such as slow system access when used simultaneously. Overall, this E-Kinerja operates as intended, thereby encouraging the improvement of employe performance, although further enhancements and training in the use of E-Kinerja are still needed for optimal results.